Autonomous action and cooperativity between the ONECUT2 transcription factor and its 3′ untranslated region - Steadman, Kenneth; You, Sungyong; Srinivas, Dustin V.; Mouakkad, Lila; Yan, Yiwu; Kim, Minhyung; Venugopal, Smrruthi V.; Tanaka, Hisashi; Freeman, Michael R. (Frontiers in Cell and Developmental Biology, 2023)
The transcription factor ONECUT2 (OC2) is a master transcriptional regulator operating in metastatic castrate-resistant prostate cancer (mCRPC) that suppresses AR activity and promotes neural differentiation and tumor cell survival. OC2 mRNA possesses an unusually long (14,575 nt), evolutionarily conserved 3’-untranslated region (3’-UTR) with many microRNA binding sites, including up to 26 miR-9 sites. This is notable because miR-9 targets many of the same genes regulated by the OC2 protein. Paradoxically, OC2 expression is high in tissues with high miR-9 expression. The length and complex secondary structure of the OC2 mRNA suggests it is a potent master competing endogenous RNA (ceRNA) capable of sequestering miRNAs. Here we describe a novel role for the OC2 3’-UTR in lethal prostate cancer consistent with a function as a ceRNA. A plausible ceRNA network in OC2-driven tumors was constructed computationally then confirmed in prostate cancer cell lines. Genes regulated by the OC2 3’-UTR exhibited high overlap (up to 45%) with genes driven by overexpression of the OC2 protein in the absence of the 3’-UTR, indicating a cooperative functional relationship between the OC2 protein and its 3’-UTR. These overlapping networks suggest an evolutionarily conserved mechanism to reinforce OC2 transcription by protection of OC2-regulated mRNAs from miRNA suppression. Both the protein and the 3’ UTR showed increased Polycomb Repressive Complex activity. Expression of OC2 3’-UTR mRNA alone (without protein) dramatically increased metastatic potential by in vitro assays. Additionally, OC2 3’-UTR increased expression of Aldo-Keto Reductase and UDP-glucuronyl transferase family genes responsible for altering the androgen synthesis pathway. ONECUT2 represents the first described dual-modality transcript that operates as both a key transcription factor driving castration resistant prostate cancer but also as a master ceRNA that promotes and protects the same transcriptional network.